Point prevalence survey to assess antibiotic prescribing pattern among hospitalized patients in a county referral hospital in Kenya - Kamita, Moses; Maina, Michael; Kimani, Racheal; Mwangi, Robert; Mureithi, Dominic; Nduta, Cynthia; Gitaka, Jesse (Frontiers in Antibiotics, 2022)
Inappropriate use of antibiotics is among the contributing factors to the development of antibiotic resistance. This resistance is driven by an inappropriate prescribing pattern by clinicians and failure to follow the guideline on antibiotic use. Antibiotic resistance leads to increased cost of health care, increased morbidity, and mortality. This study examined the prevalence of antibiotic prescription patterns among hospitalized patients in the Kiambu county referral hospital to identify opportunities for quality improvement in the hospital. The study was conducted in July 2021 and included all the patients hospitalized on the day of the study. A World Health Organization Point Prevalence Survey (PPS) tool was used to retrieve the data from patient medical files. Collected data was anonymized, entered into a customized excel sheet, validated, and then analyzed using SPSS version 26. Among the 308 surveyed patients, 191 (62%), were on antibiotic therapy. Of the total, 60.1% were female. The pediatric ward had the highest prescription rate of antibiotics at 94.1%, followed by the medical ward at 69.2%, and the gynecology ward at 65.6%. More than 40% of antibiotic prescriptions were indicated for medical prophylaxis. For the community-acquired infections, penicillin was the most prescribed antibiotic (32.2%), followed by 3rd generation cephalosporins (27.6%) and aminoglycosides (17.2%). Risk factors for inappropriate use of antibiotics (e.g., incomplete site of indication, lack of route of administration, and duration of administration) were seen in the medical and surgical ward. This study provides evidence of the high prescription rate of antibiotics, especially in pediatric patients, and an increased risk of inappropriate use of antibiotics. The finding lays a strong case for areas of intervention and implementation of antibiotic stewardship policies in Kenyan hospitals.